An Embodied Agent Learning Affordances With Intrinsic Motivations and Solving Extrinsic Tasks With Attention and One-Step Planning - Baldassarre, Gianluca; Lord, William; Granato, Giovanni; Santucci, Vieri Giuliano (Frontiers in Neurorobotics, 2019)
We propose an architecture for the open-ended learning and control of embodied agents. The architecture acquires action affordances and forward models based on intrinsic motivations and can later use the acquired knowledge to solve extrinsic tasks by decomposing them into sub-tasks each solved with one-step planning. An affordance is here operationalised as the agent's estimate of the probability of success of an action performed on a given object. The focus of the work is on the overall architecture while single sensorimotor components are simplified. A key element of the architecture is the use of `active vision' that plays two functions, namely to focus on single objects and to factorise visual information into the object appearance and object position. These processes serve both the acquisition and use of object-related affordances, and the decomposition of extrinsic goals (tasks) into multiple sub-goals (sub-tasks). The architecture gives novel contributions on three problems: (a) the learning of affordances based on intrinsic motivations; (b) the use of active vision to decompose complex extrinsic task; (c) the possible role of affordances within planning systems endowed with models of the world. The architecture is tested in a simulated stylised 2D scenario requiring to move or `manipulate' objects in order to accomplish overall configurations of the objects (extrinsic goals). The results show the utility of using intrinsic motivations to support affordance learning; the utility of active vision to solve composite tasks; and the possible utility of affordances for solving utility-based planning problems.